The nano-texturing of MgO microrods for antibacterial applications. Issue 104 (28th October 2016) - Aničić, N.; Vukomanović, M.; Suvorov, D.
Abstract : The nano-texturing of MgO microrods strongly improved their bactericidity due to optimized bacteria/surface interactions. Abstract : MgO exhibits antibacterial activity via a contact-based mechanism, which makes the design of its surface crucial. For this reason we systematically studied the effect of the calcination temperature on the morphological and antibacterial characteristics of MgO microrods. We observed the nano-texturing of the microrod's surface at calcination temperatures higher than 700 °C. The prepared particles improved the antibacterial activity against Escherichia coli ( E. coli, ATCC 47076), which was related to the enhanced contact with the bacteria. The optimal nano-texturing of the MgO microrods was achieved after calcination at 900 °C. These microrods eliminated the bacteria 75% faster than commercially available MgO nanoparticles, which we attributed to a reduced concentration of non-emissive defects at the MgO surface. In addition, the nano-textured microrods agglomerated far less than the commercial nanoparticles, which favours their further processing.